Experimental validation of double pass discrete raman amplifier limitation for large signals - M. Ali , Murtaza I.; Abdul Kadir@Jaafar, Muhammad Zamzuri; Ahmad, Ashfaq; Mohamad, Romli; Mahdi, M.A. (IEEE, 2006)
In this letter, we present a report on the experimental validation of double-pass discrete Raman amplifier (DRA) limitation for large signals. It has been proven that the limitation of double-pass Raman amplifier for large signals is due to stimulated Brillouin scattering (SBS) even though with a modulated signal at 10-Gb/s data. The multichannel amplification shows that this limitation can be relaxed due to energy distribution among the channels, the SBS threshold is enhanced. An average gain of 19.2 dB is obtained in four-channel amplification without any significant SBS effects. The double-pass DRA is found suitable for large signals to be deployed in wavelength division multiplexing systems.